Low-temperature method for desiliconization of polymetallic slags by ammonium bifluoride solution; Environmental Science and Pollution Research (ESPR); Vol. 30, iss. 11 - Smorokov A. A. Andrey Arkadievich; Kantaev A. S. Aleksandr Sergeevich; Bryankin D. V. Daniel Valerievich; Miklashevich A. Anna; Kamarou M. Maksim; Romanovski V. Valentin (2023, 2023)
Title screen